تكوين البيئة بمهارة الكلام في معهد دار السلام عيسونج سينجون جومبانج - Hayat Qoys El-Harrani El-Harrani; Burhanuddin Ubaid (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
Formation of the environment is one of the ways that students become accustomed to in their activities to carry out an obligation of expressing the command and continuing to work. Speaking skill is one of the forms of proficiency or ability that must be achieved and applied in teaching Arabic from its skills. ‌‌‌Dar Al Salam Institute is one of the institutes that is located in the city of Jombang based on the obligation to use the Arabic language in its activities. The questions of this research are how to form the environment of the Arabic language with the skill of speaking at the Institute of Dar Al-Salam Asung Sangun Jombang? What are the factors driving and inhibiting speaking skill in the environment of the Institute of Dar es Salaam Asong Sungun Jombang? What are the solutions to apply the skill of speaking in the environment of the Institute of Dar Al-Salam Asung Sengun Jombang? The research used the qualitative approach here. Method of data collection by observation, interview, and documentation. Data analysis method by data reduction, data presentation, and conclusion. The results of this research showed that the formation of the Arabic language environment with the skill of speaking in the Institute of Dar Al-Salam Asong Sengun Jombang facilitates the step and application of the members' sayings for the Arabic call all activities, including the activity of teaching the morning addition, the Navira school, and the compulsory Arabic language programs. The motives for applying this research are the abundance of Arab activities that drive the members' accuracy and response. The barriers to this application are the least of the Arabic language teachers with their quality in it, and the solutions for the application of the speaking skill.